The Teacher and the community, school culture and organizational leadership - Prieto, Nelia G.; Arcangel, Clotilde N.; Corpuz, Brenda B. (Quezon City, Metro Manila : Lorimar Publishing, Inc., 2019)
The Teacher and the community school culture and organizational leadership is aligned with the Philippine Professional Standards for Teachers (PPSTs), the standards of quality teaching in the Philippines. The PPSts consist of seven (7) domains and thirty seven (37) strands and 148 performance indicators of good teaching.
Chapter 1: Philosophical thoughts on education -- Chapter 2: Historical foundation of education -- Chapter 3: Social science theories and their implications to education -- Chapter 4: The strengths and weaknesses of the Filipino character: A socio-cultural issue -- Chapter 5: Global issues that concern schools and society -- Chapter 6: The why and how of school and community partnership -- Chapter 7: The teacher and the community: Teacher$1 (Bs ethical and professional behavior -- Chapter 8: Organizational leadership -- Chapter 9: The school head in school-based management (SBM) -- Chapter 10: Creating a positive school culture -- Chapter 11: School policies and their functions -- Chapter 12: Roles and competencies of school heads -- References -- Appendix A: Revised school-based management assessment tool -- List of Table -- List of Figure.s
Includes bibliographical references.
Keywords: TEACHING